Environmental art as an innovative medium for environmental education in Biosphere Reserves. Issue 9 (21st October 2017) - Marks, M.; Chandler, L.; Baldwin, C.
Abstract: A key goal of Biosphere Reserves (BR) is to foster environmental education for sustainable development. In this study we systematically analyse two cases in which environmental art is used as a mechanism to engage communities in 'building environmental understanding', in Noosa BR in Australia and North Devon BR in the United Kingdom. Data were derived through document analyses, site visits, questionnaires and semi-structured interviews conducted with the audience, artists, and residents. The study concludes that environmental art can build understanding through (1) exchanging ideas and providing dialogue (2) building a sense of place (3) clarifying and enhancing the understanding of information and issues, and (4) generating concern. Consequently environmental art should be considered an innovative addition to the suite of environmental education tools used in other BRs and community organisations that aim to educate about the environment.